Prayas at EmoInt 2017: An ensemble of deep neural architectures for emotion intensity prediction in tweets - Goel P.; Kulshreshtha D.; Jain P.; Shukla K.K. (My University, 2025)
The paper describes the best performing system for EmoInt - a shared task to predict the intensity of emotions in tweets. Intensity is a real valued score, between 0 and 1. The emotions are classified as - anger, fear, joy and sadness. We apply three different deep neural network based models, which approach the problem from essentially different directions. Our final performance quantified by an average pearson correlation score of 74.7 and an average spearman correlation score of 73.5 is obtained using an ensemble of the three models. We outperform the baseline model of the shared task by 9.9% and 9.4% pearson and spearman correlation scores respectively. © 2017 Association for Computational Linguistics.